O21.2 Effect of Mutations in pilQ on the Susceptibility of Neisseria Gonorrhoeae to Cephalosporins. (13th July 2013) - Trees, D; Pettus, K; Johnson, S
Abstract : Background: The susceptibility of N. gonorrhoeae to beta-lactam antibiotics is determined by mutations or the presence of mosaic sequence in penA, which codes for PBP2. The level of susceptibility is influenced by the presence of mutations in ponA, mtrR, por, and pilQ . Here we investigate the potential for isolates of N. gonorrhoeae that give elevated MIC values to both penicillin and cephalosporins to mutate to still higher MIC values. Methods: Mutations in gonococcal isolates were determined by DNA sequencing. MIC values were determined by agar dilution. Mutants exhibiting higher MIC values were selected on GC base agar that contained either a gradient or uniform concentration of cefpodoxime or ceftriaxone. Results: Examination of mutants of N. gonorrhoeae with exhibited elevated MIC values to cephalosporins revealed SPL4 3–4. Unlike previous, similar mutants, SPL4 3–4 did not possess additional mutations in penA . Genetic transformation experiments and genomic sequencing indicated the presence of a two base insertion mutation in pilQ that created a termination codon at amino acid 159 which resulted in a truncated protein and an increase in the ceftriaxone MIC from 0.03 to 0.5 ug/ml. Additional transformation and sequencing experiments using amplified pilQ DNA from SPL4 3–4 confirmed that the insertion mutation in pilQ was responsible for the increased resistance to cephalosporins as well as to penicillin. Further experimentation by amplification mutagenesis of pilQ with Taq polymerase yielded three additional pilQ mutants which exhibited increased MICs to cephalosporins, and all caused premature termination of the translation of the pilQ protein. Conclusion: Most of the studies examining increased MICs to cephalosporins in the gonococcus have focused on additional mutations in a mosaic penA gene. However, in this study we have been able to generate mutations in pilQ that resulted in increased MICs. Future studies will look for similar mutations in gonococcal clinical isolates.